2017
DOI: 10.1111/jop.12529
|View full text |Cite
|
Sign up to set email alerts
|

DNA base excision repair proteins APE‐1 and XRCC‐1 are overexpressed in oral tongue squamous cell carcinoma

Abstract: DNA base excision repair proteins APE-1 and XRCC-1 are upregulated in oral tongue squamous cell carcinoma, and XRCC-1 expression is associated with better clinical staging and nodal status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Next, another study done on almost the same set of genes but on myeloproliferative neoplasm ( n = 133) treated with hydroxyurea has established a role of BER genes in progression and clinical evolution of neoplasm (Azevedo et al 2018). Further, the study by Santana et al (2016) has shown overexpression of AP-1 and XRCC-1 in oral tongue squamous cell carcinoma ( n = 82). A high expression of XRCC-1 was significantly associated with early tumor stage.…”
Section: Dna Repair In Cancer Initiation and Progressionmentioning
confidence: 89%
“…Next, another study done on almost the same set of genes but on myeloproliferative neoplasm ( n = 133) treated with hydroxyurea has established a role of BER genes in progression and clinical evolution of neoplasm (Azevedo et al 2018). Further, the study by Santana et al (2016) has shown overexpression of AP-1 and XRCC-1 in oral tongue squamous cell carcinoma ( n = 82). A high expression of XRCC-1 was significantly associated with early tumor stage.…”
Section: Dna Repair In Cancer Initiation and Progressionmentioning
confidence: 89%
“…Smoking is the main etiological factor associated with its development. 3 Although the epidemiological profile has changed over time, with considerable regional variations, there is still higher prevalence of OTSCC among males, as they have greater exposure to risk factors. 1,3 OTSCC exhibits an aggressive biological behavior and has usually a poorer prognosis when compared to tumors at other sites.…”
Section: Introductionmentioning
confidence: 99%
“…3 Although the epidemiological profile has changed over time, with considerable regional variations, there is still higher prevalence of OTSCC among males, as they have greater exposure to risk factors. 1,3 OTSCC exhibits an aggressive biological behavior and has usually a poorer prognosis when compared to tumors at other sites. 4,5,6,7 Lower lip squamous cell carcinoma (LLSCC) is more common among male patients above the age of 50 years and solar radiation is the main etiological factor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 4 XRCC genes are involved in base excision repair (BER) and single-strand break in damaged DNA in human genome. 1 5 Molecular epidemiological studies have shown that XRCC genes are significantly associated with lung cancer, 6 9 oral cancer, 10 bladder cancer, 11 13 ovarian cancer, 14 , 15 esophageal cancer, 16 and gastric cancer. 17 23 Moreover, studies have revealed that XRCC gene polymorphism is highly variable in different ethnic populations.…”
Section: Introductionmentioning
confidence: 99%